Double population mrt lbm in an enclosure using nanofluid [electronic resource] - Farzaneh Bakhtvar, 1987- author (2014)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2014